The human resource perspective towards achieving vision 2020 / Ibrahim Abu Shah ... [et al.] - Abu Shah, Ibrahim; Zulpilip, Talib; Seh Ling, Iris Syawe; Yap, Yin; Chan, Soon Huat; Amin, Nicholas (1992)
Malaysia has to reorientate its economies in terms of trade orientation from being moderately outward oriented to that of strongly outward oriented in order to realize Vision 2020. Such reorientation requires the manufacturing sector to play a dominant role in terms of export earnings. According to the Sixth Malaysia Plan, the manufacturing sector is targeted to grow by 11.5% per annum during the Sixth Malaysia Plan period. To sustain such growth, Malaysia must be able to address the issue of an adequate supply of educated and trained labour force qualitatively and quantitatively.